Do predator energy demands or previous exposure influence protection by aposematic coloration of prey? - Veselý, Petr; Ernestová, Barbora; Nedvěd, Oldřich; Fuchs, Roman (Current zoology, 2017)
Growing evidence exists that aposematic and toxic prey may be included in a predator's diet when the predator experiences physiological stress. The tree sparrow Passer montanus is known to have a significant portion of aposematic and toxic ladybirds in its natural diet. Here, we present experiments testing the attack and eating rate of the tree sparrow toward the invasive aposematic harlequin ladybird Harmonia axyridis. We wondered whether the sparrow's ability to prey on native ladybirds predisposes them to also prey on harlequin ladybirds. We compared the attack and eating rates of tree sparrows of particular age and/or experience classes to test for any changes during ontogeny (hand-reared × young wild-caught ×adult wild-caught) and with differing perceived levels of physiological stress (summer adult × winter adult). Winter adult tree sparrows commonly attacked and ate the offered ladybirds with no evidence of disgust or metabolic difficulties after ingestion. Naïve and wild immature tree sparrows attacked the ladybirds but hesitated to eat them. Adult tree sparrows caught in the summer avoided attacking the ladybirds. These results suggest that tree sparrows are able to cope with chemicals ingested along with the ladybirds. This pre-adaptation enables them to include ladybirds in their diet; though they commonly do this only in times of shortage in insect availability (winter). Young sparrows showed avoidance toward the chemical protection of the ladybirds.
Keywords: chemical protection; toxic prey predation; warning signal; visual signal